Response to tyrosine kinase inhibitors in myeloid neoplasms associated with PCM1‐JAK2, BCR‐JAK2 and ETV6‐ABL1 fusion genes. Issue 7 (28th April 2020) - Schwaab, Juliana; Naumann, Nicole; Luebke, Johannes; Jawhar, Mohamad; Somervaille, Tim C.P.; Williams, Mark S.; Frewin, Rebecca; Jost, Philipp J.; Lichtenegger, Felix S.; La Rosée, Paul; Storch, Nicola; Haferlach, Torsten; et al.
Abstract: We report on 18 patients with myeloid neoplasms and associated tyrosine kinase (TK) fusion genes on treatment with the TK inhibitors (TKI) ruxolitinib ( PCM1‐JAK2, n = 8; BCR‐JAK2, n = 1) and imatinib, nilotinib or dasatinib ( ETV6‐ABL1, n = 9). On ruxolitinib (median 24 months, range 2‐36 months), a complete hematologic response (CHR) and complete cytogenetic response (CCR) was achieved by five of nine and two of nine patients, respectively. However, ruxolitinib was stopped in eight of nine patients because of primary resistance (n = 3), progression (n = 3) or planned allogeneic stem cell transplantation (allo SCT, n = 2). At a median of 36 months (range 4‐78 months) from diagnosis, five of nine patients are alive: four of six patients after allo SCT and one patient who remains on ruxolitinib. In ETV6‐ABL1 positive patients, a durable CHR was achieved by four of nine patients (imatinib with one of five, nilotinib with two of three, dasatinib with one of one). Because of inadequate efficacy (lack of hematological and/or cytogenetic/molecular response), six of nine patients (imatinib, n = 5; nilotinib, n = 1) were switched to nilotinib or dasatinib. At a median of 23 months (range 3‐60 months) from diagnosis, five of nine patients are in CCR or complete molecular response (nilotinib, n = 2; dasatinib, n = 2; allo SCT, n = 1) while two of nine patients have died. We conclude that (a) responses on ruxolitinib may only be transient in the majority of JAK2 fusion gene positive patients with allo SCT being an important early treatment option, and (b) nilotinib or dasatinib may be more effective than imatinib to induce durable complete remissions in ETV6‐ABL1 positive patients.